Implementation of pharmacist recommendations following medication reviews in aged care - Ramsey, Noah C.; Peterson, Gregory M.; Mirkazemi, Corinne; Salahudeen, Mohammed S. (Frontiers in Pharmacology, 2025)
BackgroundResidential medication management reviews (RMMRs) are a government-funded program in Australia, designed to optimise medication use and enhance safety in aged care residents through reviews conducted by credentialed pharmacists. However, variability in general practitioners’ (GPs) implementation of pharmacists’ recommendations may limit their effectiveness. This study investigated the recommendations made by pharmacists during RMMRs, and the aspects of the recommendations that were associated with their subsequent implementation by GPs.MethodsThis retrospective study analysed RMMRs from 54 aged care facilities across Tasmania, Australia between January 2020 and December 2023. Residents with at least two RMMRs spaced approximately 12 months apart were included, with data extracted from the earliest eligible RMMR as the index. Data sources included medication profiles, residents’ clinical histories, RMMR reports, GP feedback forms, and follow-up RMMRs.ResultsOf the 1646 index RMMRs analysed, 3774 recommendations were made (median: 2 per RMMR), with 50% (n = 1872) fully implemented by the next RMMR 12 months later. Most recommendations (91%, n = 3380) involved a change in therapy, primarily medicine cessation (49%, n = 1810) or dose reduction (21%, n = 799), with implementation rates of 51% and 49%, respectively. Common deprescribing targets included colecalciferol (n = 318, 37% implemented), proton pump inhibitors (n = 123, 43% implemented), statins (n = 145, 48% implemented), and low-dose aspirin (n = 107, 63% implemented). One in six recommendations involved a potentially inappropriate medicine (PIM) according to an Australian resource, such as antipsychotics, benzodiazepines, and opioids. Implementation rates were comparable between deprescribing of PIMs and non-PIMs (51% vs. 50%, p > 0.9). Monitoring-related recommendations were significantly more likely to be implemented than those involving a change in therapy (73% vs. 48%, p < 0.001).ConclusionHalf of all recommendations were implemented by GPs within 12 months, with most targeting the deprescribing of preventive or high-risk medicines. Future research should identify which recommendations GPs prioritise and the factors influencing their implementation of pharmacists’ medication review recommendations, in order to enhance the effectiveness of RMMRs in aged care.